2016
DOI: 10.1002/alr.21875
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal adenoid cystic carcinoma: a population‐based analysis of 694 cases

Abstract: This study represents the largest cohort of SNACC patients to date. Factors that confer a survival benefit in SNACC include M0 disease, and presentation primarily in the nasal cavity. Overall low rates of nodal metastasis may not warrant the use of elective neck dissections, unless there is clinical suspicion. Modalities of therapy that include surgery greatly improve survival. Adjuvant radiotherapy appears to slightly improve 5-year disease-free survival but does not impact long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 41 publications
7
27
1
Order By: Relevance
“…Common presenting symptoms of SNACC include maxillary pain/pressure, unilateral nasal blockage, and recurrent epistaxis . Consistent with other studies, including large database analyses, this study found that SNACCs most commonly occur within the maxillary sinus (49.7%) followed by the nasal cavity (32.4%) . It is thus important to assess for perineural invasion for all maxillary sinus tumors (eg, cheek numbness) due to the predilection of SNACC to track along the infraorbital nerve.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Common presenting symptoms of SNACC include maxillary pain/pressure, unilateral nasal blockage, and recurrent epistaxis . Consistent with other studies, including large database analyses, this study found that SNACCs most commonly occur within the maxillary sinus (49.7%) followed by the nasal cavity (32.4%) . It is thus important to assess for perineural invasion for all maxillary sinus tumors (eg, cheek numbness) due to the predilection of SNACC to track along the infraorbital nerve.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, 49.1% of patients presented with stage IV disease, further illustrating the possibility of presenting with significant tumor spread. In contrast to other head and neck ACCs, presentation of SNACC with nodal disease and distant metastases was less common (3.6% and 3.7%, respectively), likely due to the scarce lymphatic drainage patterns of the sinonasal tract …”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations